2022
DOI: 10.1073/pnas.2204901119
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in Kcnc3 causes hippocampal learning deficits in mice

Abstract: Although a wide variety of genetic tools has been developed to study learning and memory, the molecular basis of memory encoding remains incompletely understood. Here, we undertook an unbiased approach to identify novel genes critical for memory encoding. From a large-scale, in vivo mutagenesis screen using contextual fear conditioning, we isolated in mice a mutant, named Clueless , with spatial learning deficits. A causative missense mutation (G434V) was found in the voltage-gated pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The FOXP family proteins were also found to regulate KCNC3, KCNQ3, SLC12A4, SLC4A9, and TRPM2. KCNC3, KCNQ3, and KCNMA1 are voltage-gated potassium ion channel proteins, and the downregulation of KCNC3 and KCNQ3 in yak lungs suggested that the expression of voltage-gated potassium ion channels decreases in yaks with age, reducing membrane depolarization and harmful effects of pulmonary edema ( 29 , 30 ). KCNMA1 upregulation might be associated with its role in promoting vascular endothelial cell growth ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FOXP family proteins were also found to regulate KCNC3, KCNQ3, SLC12A4, SLC4A9, and TRPM2. KCNC3, KCNQ3, and KCNMA1 are voltage-gated potassium ion channel proteins, and the downregulation of KCNC3 and KCNQ3 in yak lungs suggested that the expression of voltage-gated potassium ion channels decreases in yaks with age, reducing membrane depolarization and harmful effects of pulmonary edema ( 29 , 30 ). KCNMA1 upregulation might be associated with its role in promoting vascular endothelial cell growth ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%